2011
DOI: 10.3171/2010.12.focus10255
|View full text |Cite
|
Sign up to set email alerts
|

Management of cerebrospinal fluid leaks after anterior decompression for ossification of the posterior longitudinal ligament: a review of the literature

Abstract: Object Anterior decompression is an effective way to treat cervical myelopathy associated with ossification of the posterior longitudinal ligament (OPLL); however, this approach is associated with an increased risk of a dural tear and resultant CSF leak because fusion of the dura with the ossified PLL is common in these cases. The authors review the literature and present an algorithm for treatment of CSF leaks in these patients. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 68 publications
0
54
1
Order By: Relevance
“…When the pathologic focus is localized below the 3rd-4th cervical vertebrae, a direct anterior approach to the pathology can lead to a good result, but the risk of spinal cord injury is high and in the case that OPLL is not separated from the dura mater, there is a risk of developing complications such as a dural tear or CSF leakage [31,32]. …”
Section: Anterior Approachmentioning
confidence: 99%
“…When the pathologic focus is localized below the 3rd-4th cervical vertebrae, a direct anterior approach to the pathology can lead to a good result, but the risk of spinal cord injury is high and in the case that OPLL is not separated from the dura mater, there is a risk of developing complications such as a dural tear or CSF leakage [31,32]. …”
Section: Anterior Approachmentioning
confidence: 99%
“…The incidence of CSF leakage in the anterior approach has been estimated to range from 4.3% to 32%. [15] In the present case, the rapidly progressive nature of the myelopathy motivated an anterior surgical approach; whereas slow onset, progressive symptoms in the context of OPLL would motivate long-segment posterior decompression and fusion.…”
Section: Discussionmentioning
confidence: 90%
“…[15] While observation of asymptomatic OPLL remains the standard of care, symptomatic canal stenosis caused by OPLL can require surgery. [22] Anterior decompression of the ventrally located pathology is often indicated and has shown lower rates of symptom recurrence, but higher rates of postoperative complications.…”
Section: Discussionmentioning
confidence: 99%
“…1,9 These complications included the risk of a dural tear or CSF leakage, which was difficult to repair in anterior cervical surgery. 2,13 The incidence of dural tear and CSF leakage has been reported to be 13.7-fold greater in patients with OPLL compared with patients affected by other conditions. 8 It has also been reported that CSF leakage frequently occurs when a double-layer sign can be identified by a CT scan, which also occurred in our cases (Fig.…”
Section: Discussionmentioning
confidence: 99%